PSIII-12 Effect of PRRSV infection during gestation on sickness behaviors in the piglets after immune challenge - Rymut, Haley E (J Anim Sci, 2019)
Porcine reproductive and respiratory syndrome virus (PRRSV) costs the U.S. pork industry millions of dollars yearly due to production losses and management costs. The objective of this study was to evaluate the effects of maternal immune activation (MIA) elicited by PRRSV infection during gestation on the behavioral response of the offspring to subsequent immune challenge. On gestational day 76, PRRSV negative Camborough gilts (n = 6) were either inoculated with PRRSV or saline intranasally. Nineteen female and male piglets from these PRRSV positive and Control gilts were weaned at day 21 and subsequently housed in groups. At day 60, piglets were randomized by sex to receive either saline or an intraperitoneal injection of Poly(I:C) to represent immune challenge. Poly(I:C) is a synthetic polyinosinic-polycytidylic acid that mimics double-stranded RNA that activates host defense similar to viral infections by stimulating the release of cytotoxic cytokines and inducing interferon-gamma production. Post injection, binary laying, eating, vomiting, panting, and overall sickness behaviors were collected by instantaneous scan sampling at 1.5-minute intervals for 60 minutes by a trained experimenter blinded to the experimental design. Fisher’s exact test and Cochran-Mantel-Haenszel statistics were used to test the effects of gilt treatment, piglet challenge, and sex within and across factor levels. Male piglets from PRRSV-treated gilts exhibited significantly (P < 0.0455) fewer sickness behaviors than piglets from control gilts between 31 and 45 minutes post-challenge. Significant associations between gilt treatment and both panting (P < 0.0162) and overall sickness behavior (P < 0.0245), while controlling for sex and piglet challenge, were observed. This study characterized the MIA and sex-dependent nature of the effect Poly(I:C) immune challenge on behavior. Our results indicate that MIA is correlated to increased behavioral response to secondary viral infection in male offspring. This study is supported by USDA NIFA AFRI, grant number 2018-67015-27413.